Population Coalition Policy as an Effort to Strengthen Population, Family Planning and Family Development Programs in Central Java Province - Nurani Ajeng Tri Utami (Jurnal Dinamika Hukum, 2020)
Population problems have broad dimensional aspects so that partnerships are needed with the formation of Population Coalition. Central Java Province is one of the provinces in Indonesia which has a Population Coalition based on Decree of the General Chairperson of the Indonesian Coalition for Population and Development Number: 002/SK/KK-PROV/III/2019. Therefore, it is very important to examine the implementation of Population Coalition policies and the factors that influence their implementation at the provincial level. This research is qualitative research with a sociological juridical approach. The results showed that the Population Coalition policies in Central Java Province have been implemented under collaboration with the Youth Population Coalition and various related institutions/stakeholders in strengthening the Population, Family Planning, and Family Development programs. The factors that influence the implementation of the Central Java Province Population Committee regulation, facilities, and infrastructure, as well as community and cultural factors that still do not care about population problems.Keywords: Policy, Population Coalition, Population Program, Family Planning, Family Development.